A mild, general, and metal-free method for site-specific deuteration induced by visible light using D2O as the source of deuterium atoms. Issue 3 (27th January 2020) - Shi, Shuai; Li, Ruining; Rao, Liangming; Sun, Zhankui
Abstract : Visible light induced desulfurization–deuteration method was developed using D2 O as the source of deuterium atoms. This radical approach features mild conditions, broad substrate scope, highly efficient D-incorporation and excellent functional group compatibility. Abstract : A radical deuteration procedure using D2 O as the source of deuterium atoms is strongly preferred in terms of mildness, sustainability, and cost. Herein, we disclose a radical approach for site-specific, highly efficient and metal-free deuteration using D2 O under visible light conditions. This desulfurization–deuteration strategy features mild conditions, broad substrate scope, highly efficient D-incorporation, excellent functional group compatibility, sustainable energy and is hardly affected by substrate steric factors.